Serbuk Daun Jambu Biji Memperbaiki Performans Pertumbuhan dan Morfologi Duodenum Ayam Jawa Super (GUAVA LEAF POWDER IMPROVING PERFORMANCE OF GROWTH AND DUODENUM MORPHOLOGY OF JAWA SUPER CHICKEN) - Setiawan, Haris; Utami, Listiatie Budi; Zulfikar, Muhammad (Jurnal Veteriner, 2019)
Natural bioactive compounds used as feed supplements in feed could increase chicken productivity in the livestock industry. The research aims to study the use of guava leaf powder as a source of bioactive compounds in the feed on growth performance and duodenum morphology of Jawa Super Chicken. This study used 80 days old chick (DOC) Jawa Super chickens reared until the age of 16 days. The study used a completely randomized design, with the addition of treatments guava leaf powder in the basal feed from 0 g/kg diet (control); 2.5 g/kg of feed (P1); 5 g/kg of feed (P2); 10 g/kg of feed (P3). Parameters observed included growth performance, body components, digestive organ components and duodenum morphology consisting of crypt depth, height, and area of villi. Data was analyzed by using one-way analysis of variance then continued with LSD and Duncan test (Pd”0.05). The results showed that guava leaf powder could significantly increase the height of villi, and components of digestive organs in chickens. The results of the duodenum morphology observation showed that the P2 and P3 are better than the control (Pd”0.05). The growth performance and body components of the Jawa Super chicken did not show a significant difference (Pd”0.05) between the control and the treatment. In conclusion, the guava leaf powder with a dose of 10 g/kg body weight can increase duodenal villi growth, the weight of intestine and liver without influence the weight of Jawa Super chickens aged 16 days.